FUNGSI NEGARA DALAM PERJANJIAN KERJA BERSAMA PERBURUHAN - Akhyar, Zainul (Jurnal Pendidikan Kewarganegaraan, 2016)
Involvement of the country in employment case related with function and duty of the country/government is how to create, to look after, to maintain, and to increase the orderliness of social condition that to flow into public service. So, the function of country (government) basically is the function of public service. The definition of duty of the country in macro context is to do the policies to get the goal of the country governance, and the country governance basically is the national goal of its country.Involvement of the country (government) in law context about employment is to create fair employment relationship to become a part of function and duty of the government. However, if the relationship between worker and boss/entrepreneur that very different in social economy is delivered to all sides, so the goal to create social justice in life society is very difficult to get, because the strong side will be always control the weak side, that case already become an adagio, which the strong and authorized side will inclined to delude the weak side. Because of that, the weak side should be get protection from the country.In context of collective work agreement, the involvement of the country is a rule of legislation that should be bothered, concerning the system of remunerating (mulberry minimum such as UMR), health, working safety, and others, basically those as a part of government duty in running of function of politicalÂ  that including in formula of national goal in Indonesian Republic that loaded in fourth paragraph of opening of UUD 1945, that is âto create social justice and to move forward public prosperity for socialize and for Indonesian nation.Â Key Words: Function of Country, Collective work agreement